Local structural properties of the partly quenched multi component ionic liquids - Uygun, M.; Tatlipinar, H. (AMER INST PHYSICS, 2007)
Integral equation technique to calculate local structure of liquids in full equilibrium is based on the Ornstein-Zernike (O-Z) integral equations with appropriate closures. This theory recently extended to some non-equilibrium processes where system consist of frozen and annealed components. By using Hypernetted-Chain approximation (O-Z) equations are solved numerically for both fully equilibrium and partly quenched systems. As an example NaCl, AlCl3 and YCl3 metal chlorides are studied. Main attention is given on local structure and intermediate range order by comparing liquid and partly quenched states. The results of structural quenching are a reduction in short range order and enhancement of intermediate range order in metal ion component. (O-Z) equations for partly quenched three component systems are derived end applications are discussed.
Keywords: ionic liquids; integral equations; partly quenched liquids.; Physics